Социотип личности как фактор влияющий на продуктивность совместной деятельности в командообразовании - Григорова, Ю.Б.; Маканова, А.Ж. (My University, 2016)
his article is devoted to the influence of personality type on the productivity of joint activities. A feature article is the use of socionic methods for the formation of groups engaged in joint activities
Keywords: Socionics; system interaction; the information space; the type of information metabolism